Creative Process of Children's Drawing in the Padhang Njingglang Learning Community with the Happy Memory Activation Method - Sidyawati, Lisa; Hartono, Hartono; Syakir, Syakir; Prasetyo, Anang (Gorga : Jurnal Seni Rupa, 2024)
Education is the leading force in human life, according to Kant's statement that humans can only become human through education. Humanistic education empowers individuals by fostering intellectual, emotional, and spiritual development. Art education, particularly within this community, serves as a tool to balance these aspects, promoting harmonious personality development. The Padhang Njingglang Community, founded by Anang Prasetyo in Tulungagung in 2008, targets children who are often overly reliant on digital technology and exhibit behavioral issues such as a lack of politeness and reduced engagement in traditional play. The role of the Padhang Njingglang Community is essential in addressing behavioral challenges among Generation Alpha children through humanistic art education. The community employs the "Happy Memory Activation" method, encouraging children to recall and express happy memories through drawing. This method helps children build self-confidence, enhance creativity, develop emotional awareness, and foster positive character traits. Research on this community is necessary because it emphasizes arts education and spiritual aspects, so it needs to be explored further. The study employs a qualitative phenomenology approach, utilizing data from interviews, observations, and children’s artworks to deeply understand the impact of this educational model.  Findings suggest that when combined with humanistic principles, art can be a transformative medium for childhood education, providing emotional and psychological benefits that extend into adulthood. The Padhang Njingglang Community exemplifies how integrating art into education can effectively address the unique challenges of modern childhood, especially in the digital age.